The Retina in Health and Disease - Ptito, Maurice; Bouskila, Joseph (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Vision is the most important sense in higher mammals. The retina is the first step in visual processing and the window to the brain. It is not surprising that problems arising in the retina lead to moderate to severe visual impairments. We offer here a collection of reviews as well as original papers dealing with various aspects of retinal function as well as dysfunction. New approaches in retinal research are described, such as the expression and localization of the endocannabinoid system in the normal retina and the role of cannabinoid receptors that could offer new avenues of research in the development of potential treatments for retinal diseases. Moreover, new insights are offered in advancing knowledge towards the prevention and cure of visual pathologies, mainly AMD, RP, and diabetic retinopathy.